RANCANG BANGUN WEBSITE SORAKETRIP UNTUK OBJEK WISATA PANTAI SORAKE - Muhammad Rafiq Sitepu; Rin Rin Meilani Salim; Hita Hita (Seminar Nasional Informatika (SEMNASIF), 2020)
AbstractTourism is increasingly in demand by the community and is increasingly being developed. One of the tourist areas in Indonesia that has the potential to be developed is the Sorake Beach area, precisely located in Teluk Dalam District, South Nias Regency. This area has the potential to be one of the most influential tourist objects for the economy of the surrounding community, namely in terms of income through businesses managed by the surrounding community, such as lodging, transportation, special food and souvenirs. However, tourism publicity and information technology are still an obstacle to tourism in the Sorake Beach area. In general, tourists who know the tourist objects in this area are surfers, so it is still rare for the wider community to know what tourist objects are in this area besides surfing. This happens because there is no media that provides complete information on the travel needs of this specific area. Therefore, to meet these needs, we need a website for the Sorake Beach area. SorakeTrip is one of the websites in which there is information and travel needs specifically for the Sorake Beach area only. The research methodology used is the System Development Life Cycle up to the fifth stage. The website will be built for admin, visitor and customer access rights that have features to manage the provision of information, bookings and payments for tour packages, tour guides, restaurants, transportation, and hotels. Due to the absence of a website that introduces Sorake beach, if this website is implemented it will help increase tourists and the economy of the surrounding community.Keywords : Tourism Website, Sorake Beach, SorakeTripPariwisata kian hari semakin diminati masyarakat dan makin dikembangkan. Salah satu daerah wisata di Indonesia yang memiliki potensi untuk dikembangkan adalah daerah kawasan Pantai Sorake tepatnya yang berada di Kecamatan Teluk Dalam, Kabupaten Nias Selatan. Kawasan ini sangat berpotensi sebagai salah satu objek wisata yang sangat berpengaruh bagi perekonomian masyarakat sekitar yaitu dalam hal pendapatan melalui bisnis yang dikelola oleh masyarakat sekitar, seperti penginapan, transportasi, makanan khas dan oleh-oleh. Akan tetapi, publisitas pariwisata dan teknologi informasi masih menjadi hambatan bagi pariwisata di kawasan Pantai Sorake ini. Pada umumnya wisatawan yang mengetahui objek wisata yang ada di kawasan ini adalah para peselancar sehingga masih jarang masyarakat luas yang mengetahui apa saja objek wisata yang ada di kawasan ini selain berselancar. Hal itu terjadi dikarenakan belum adanya media yang menyediakan informasi kebutuhan perjalanan wisata yang dikhususkan untuk kawasan ini secara lengkap. Maka dari itu, untuk memenuhi kebutuhan tersebut diperlukannya sebuah website untuk kawasan Pantai Sorake. SorakeTrip adalah salah satu website yang di dalamnya terdapat informasi dan kebutuhan perjalanan wisata yang dikhususkan untuk kawasan Pantai Sorake saja. Metodologi penelitian yang digunakan adalah Siklus Hidup Pengembangan Sistem hingga tahap kelima. Website akan dibangun untuk hak akses admin, pengunjung dan pelanggan yang memiliki fitur untuk mengelola penyediaan informasi, pemesanan hingga pembayaran paket wisata, pemandu wisata, restoran, transportasi, dan hotel. Dikarenakan belum adanya website yang mengenalkan pantai Sorake maka jika website ini diimplementasikan akan membantu meningkatkan wisatawan dan perekonomian masyarakat sekitar.Kata Kunci : Website Pariwisata, Pantai Sorake, SorakeTrip